1996
DOI: 10.1063/1.362120
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature magnetic properties of TbCu7-type SmCo-based films

Abstract: In applications where large remanent moments and energy products are required at elevated temperatures, SmCo-based permanent magnets provide the best properties. In addition to their high Curie points, these SmCo-based ordered phases of 1-5, 2-17, and the disordered 1-7 phase show large uniaxial anisotropies at elevated temperatures. We have now measured the high-temperature hysteresis properties of single-phase TbCu7-type SmCo-based permanent magnet films. Such single-phase samples have the advantage that opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Amorphous, CaCu 5 -, Th 2 Zn 17 -and TbCu 7 -type SmCo-based films were synthesized by sputtering (Chen et al 1993, Rani et al 1997. Single phase TbCu 7type films of composition Sm 13 Co 58 Fe 20 Cu 7 Zr 2 were sputter synthesized such that the crystallite c-axes were oriented in the film plane (Hegde et al 1996). The magnetic and crystallographic properties of these films as a function of sputter deposition parameters were studied by Hegde et al (1994).…”
Section: Sputteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous, CaCu 5 -, Th 2 Zn 17 -and TbCu 7 -type SmCo-based films were synthesized by sputtering (Chen et al 1993, Rani et al 1997. Single phase TbCu 7type films of composition Sm 13 Co 58 Fe 20 Cu 7 Zr 2 were sputter synthesized such that the crystallite c-axes were oriented in the film plane (Hegde et al 1996). The magnetic and crystallographic properties of these films as a function of sputter deposition parameters were studied by Hegde et al (1994).…”
Section: Sputteringmentioning
confidence: 99%
“…In addition to their high Curie temperatures, the SmCobased amorphous films as well as the SmCo-based ordered phases of 1:5, 2:17, and the disordered 1:7 phase show large uniaxial anisotropies at elevated temperatures (Chen et al 1993, Hegde et al 1994, Rani et al 1997. The advantage of the single phase TbCu 7 -type SmCobased permanent magnet films is that optimal magnetic properties can be obtained from the as-sputtered films without any subsequent heat treatments (Hegde et al 1996). The net anisotropy field of the films remained larger than the maximum applied field of 18 kOe even at the highest measurement temperature of 460 • C. The in-plane coercivity showed a monotonic decrease from 6.0 kOe at room temperature to 1.3 kOe at 460 • C. Figure 26 show magnetic hysteresis loops at 50 • C, for measurements inplane and perpendicular to the file plane.…”
Section: Coercivity and Energy Productmentioning
confidence: 99%
“…RE-Co (RE = rare earth) magnets have attracted the magnetic community since their discovery in the late 1960s because of their fascinating intrinsic and extrinsic magnetic properties. Owing to the high Curie temperature, RE-Co compounds with high cobalt content take a leading role in the development of permanent magnets for high temperature applications, which has been intensified in recent years [1][2][3][4][5][6][7]. Among the RE-Co family, the RECo 7 structure (TbCu 7 type) often possesses the best combination of intrinsic properties (high Curie temperature T C , high uniaxial anisotropy and high saturation polarization) and is thus an obvious choice for permanent magnet development.…”
Section: Introductionmentioning
confidence: 99%
“…The SmCo based films had a nominal composition of Sm 0.13 Co 0.58 Fe 0.20 Cu 0.07 Zr 0.02 . (Hegde 1996) This composition for bulk magnets corresponds to that normally designated as SmCo 2-17 magnets. (Parker, 1990) When films are directly crystallized onto heated substrates with this composition it has been extensively shown that the films can be formed as a single phase deposit with the TbCu 7 -type structure.…”
Section: Introductionmentioning
confidence: 94%